Optimal Waist Circumference Cutoff Values for the Diagnosis of Abdominal Obesity in Korean Adults - Yoon, Yeong Sook (Endocrinol Metab (Seoul), 2014)
Abdominal obesity is associated closely with insulin resistance, diabetes, and cardiovascular disease. Waist circumference (WC) is a useful surrogate marker commonly used for abdominal adiposity. The determination of WC cutoff levels is important in the prevention and treatment of obesity, type 2 diabetes, and related cardiovascular diseases. Recent epidemiological evidence suggested that appropriate optimal cutoffs for Koreans ranged over 80 to 89.8 cm in males and 76.1 to 86.5 cm in females. We analyzed the data from two large cohorts using receiver operating characteristic curve analysis with the incidences of diabetes, hypertension, dyslipidemia, cerebrovascular disease, myocardial infarct, angina, coronary artery disease, and multiple metabolic risk factors as outcome variables. Optimal WC cutoff points for Koreans were 85 cm in males and 80 cm in females. However, considering the prevalence of abdominal obesity and the health costs for its prevention and management, 90 cm in males and 85 cm in females are probably more appropriate thresholds for abdominal obesity. These values may be modified once better research is performed through prospective studies using representative populations, common health outcomes, and proper analytical approaches.